Photochemical smog introduction and episode selection for the ground-level ozone in Hanoi, Vietnam - Anh, Dam Duy; Co, Hoang Xuan; Kim Oanh, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 4, 2008)
Abstract